(untitled) (Jurnal Kesehatan Komunitas, 2021)
One of nutritional problems experienced by toddlers is stunting, which is a short or very short body condition in children due to chronic malnutrition that occurs from pregnant women to children aged 2 years. Nutrition education is a method and effort to increase knowledge of nutrition and eating behavior in order to create optimal nutritional status. Education for the â€œMy Plateâ€ poster is important for pregnant women to implement a healthy diet and to meet daily nutritional needs as an effort to prevent stunting. This research was conducted by interview method. From the result of this research, a poster of â€œMy Plate-Pregnant Womenâ€ has been designed as a nutrition education media. Keywords: Nutriotion Education Poster, Pregnant Women, Stunting